Asymmetric Hydroalkoxylation of Non‐Activated Alkenes: Titanium‐Catalyzed Cycloisomerization of Allylphenols at High Temperatures1. (3rd February 2015) - Schlüter, Johannes; Blazejak, Max; Boeck, Florian; Hintermann, Lukas
Abstract The asymmetric catalytic addition of alcohols (phenols) to non‐activated alkenes has been realized through the cycloisomerization of 2‐allylphenols to 2‐methyl‐2, 3‐dihydrobenzofurans (2‐methylcoumarans). The reaction was catalyzed by a chiral titanium–carboxylate complex at uncommonly high temperatures for asymmetric catalytic reactions. The catalyst was generated by mixing titanium isopropoxide, the chiral ligand (aS)‐1‐(2‐methoxy‐1‐naphthyl)‐2‐naphthoic acid or its derivatives, and a co‐catalytic amount of water in a ratio of 1:1:1 (5 mol % each). This homogeneous thermal catalysis (HOT‐CAT) gave various (S)‐2‐methylcoumarans with yields of up to 90 % and in up to 85 % ee at 240 °C, and in 87 % ee at 220 °C.